Optical sensing material for pH detection based on the use of roselle extract - Karim, NHA; Ahmad, M; Osman, M; Mokhtar, HM; Mokhtar, AM (Univ Kebangsaan Malaysia, 2024)
This research assessed the potential of natural colour extract of Hibiscus sabdariffa L. (roselle) as sensing material. The pH sensor was developed based on the use of natural reddish colour in roselle calyx, delphinidin-3-sambubioside immobilised in a glass fibre filter paper. In free solution, roselle extract was characterised by using UV-visible spectrophotometer to study the effect of pH, extract concentration, response time, repeatability and photostability. The study showed that natural colour extract can be used as sensing material for the development of an optical pH sensor.